Viscous Population Equilibria - Roger B. Myerson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
Viscosity in a biological population is the tendency of individuals to have a higher rate of interactions with their closer relatives than with similar numbers of more distantly related individuals. This paper presents a simple method of equilibrium analysis to predict the effect of viscosity in biological games. Taking the limit as viscosity goes to zero, a set of fluid population equilibria is defined. The set of fluid population equilibria is nonempty and includes all evolutionary stable strategies.
Keywords: 330